2020
DOI: 10.3390/land9060175
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Landscape and Tourism in Marginal Areas: The Case of Land Consolidation Associations in the North-West of Italy

Abstract: Land fragmentation is a factor that limits the development of the agricultural and forestry sector, as well as the ability of operators to reach a profitable economic dimension. This phenomenon also influences the creation of activities and incomes in a negative way in marginal areas. In this context, land consolidation associations (LCA) can be a useful tool in reducing this limitation and promoting better management of the territory by improving the link between the landscape and tourism. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…Specific attention to the needs and perceptions of fishermen seems necessary, due to their reluctance for a CBT development, since a special care must be taken in order to not displace local economic activities. In a general historical context in which vulnerable local communities have frequently been displaced from areas selected for environmental protection or their access to natural resources has been restricted [69,[86][87][88][89], we highlight the importance of the participation of all local actors in the proposals for land planning and sustainable management of the territory in order to ensure both the social and economic benefits of tourism flow to the communities, as well as the environmental conservation [90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…Specific attention to the needs and perceptions of fishermen seems necessary, due to their reluctance for a CBT development, since a special care must be taken in order to not displace local economic activities. In a general historical context in which vulnerable local communities have frequently been displaced from areas selected for environmental protection or their access to natural resources has been restricted [69,[86][87][88][89], we highlight the importance of the participation of all local actors in the proposals for land planning and sustainable management of the territory in order to ensure both the social and economic benefits of tourism flow to the communities, as well as the environmental conservation [90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…Heslinga et al [35] highlights tourism as valuable, insofar it encourages contextual sustainable development (SD). Tourism and nature protection initiatives are not isolated from the greater societal context; they depend on public and official awareness, acceptance, and support [71,72]. Following that argument, Heslinga et al [35] identified eight policy recommendations for stimulating synergies between tourism and landscape: understanding the historical institutional context of the region; strive for integrated policy aimed at synergetic interactions; gain an overview of all stakeholders; include all stakeholders; develop a shared story; co-create a vision for the future; allow for flexibility in the local implementation; and dare to experiment.…”
Section: Stimulating Synergies Between Tourism and Landscapementioning
confidence: 99%
“…Marinas are a driving force of economic wealth [10,11]. A characteristic landscape should enhance a territory and its tourist appeal as a tourism image [12][13][14]. Thus, a landscape in a marina including an environmental quality and scenic views should be able to gain economic benefits [15,16].…”
Section: Introductionmentioning
confidence: 99%